Educational excellence in the Islamic world : enhancing global quality and strategy planning - Berghout, Abdul Aziz (al-Amanah al-'Ammah li-Ittihad al-Jami'at al-'Arabiyah, 2011)
This paper addresses the role of both global quality and strategic planning in the process of enhancing educational excellence and creating value and opportunities for sustainable development.The paper posits that global quality aims at creating global value added to serve global stakeholders & customers in line with global standards. Hence, what is required at this stage of development of our institutions of higher education is clear and integrated framework that outlines the various aspects of global quality as an activity and process which aspires towards transforming institutions so as to attain the capabilities and strengths needed to bring home global quality as reality, culture, system and practices. For any institution to achieve this status of excellence there are certain critical success factors that need to be addressed such as; global quality teaching & learning, global quality research & innovation, global quality scholarship & human capital, global quality facilities & services, global ICT structures, global information & knowledge capital and global financial agility & sustainability. The paper concludes that there is a need to bridging localglobal talents, benchmarking for value creation, engaging stakeholders, engaging talents & creative minds, engaging global networks and educational alliances, valorizing community service & engagement and creating opportunities for financial & social investment. Besides, for any institutions of higher education to move the value chain of creating global quality, it should address matters related to the system, governance and management namely; strategic thinking, planningactioning& measurement capabilities, governance, leadership & management dynamism, dynamic quality management structure and system, autonomy, accountability & self-value creation & innovation.